INVESTIGATION OF ANTI-INFLAMMATORY AND ANTINOCICEPTIVE EFFECTS OF AQUEOUS EXTRACTS OF ARTEMISIA AFRA IN WISTAR RATS - Gondwe, Mavuto; Mpalala, Anda; Zongo, Lusanda; Kamadyaapa, David; Ndebia, Eugene; Sewani-rusike, Constance; Shauli, Mathulo; Iputo, Jehu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the anti-inflammatory and antinociceptive effects of Artemisia afra. Methods: Animals were randomly divided into five groups of six animals each and administered with normal saline (2 ml/kg), indomethacin (10 mg/ kg), and A. afra at doses of 100, 200, and 400 mg/kg, respectively. For the anti-inflammatory activity, carrageenan-induced paw edema was used while the hot plate and acetic acid induced-writhing tests were used to assess the antinociceptive activity. Results: Pretreatment with A. afra at a dose of 100 mg/kg did not show any significant biological effects (p>0.05) for any of the three tests, when compared against saline-treated control group. At a dose of 200 mg/kg, A. afra demonstrated significant effects (p<0.01), during the 5th h reducing carrageenan-induced paw edema by 12%. The highest dose (400 mg/kg) of A. afra demonstrated more potent effects by decreasing the carrageenan-induced paw swelling (p<0.001–0.05) during the 3rd, 4th, and 5th h, by up to 38% when compared against saline-treated control group. Both the 200 and 400 mg/kg, A. afra doses achieved a significant increase (p<0.05) in reaction time in the hot plate test. In the acetic acid-induced writhing test, pretreatment with A. afra (400 mg/kg) significantly reduced pain by 39% (p<0.01) by comparison with the saline control. Conclusion: Experimental data demonstrated that aqueous extract of A. afra possesses anti-inflammatory and antinociceptive properties in experimental acute inflammation and pain. These findings support the usage of A. afra in managing inflammation and pain in traditional practice.